Asian development outlook 2016 Asia's potential growth (Asian Development Bank, 2016)
"This edition highlights the need to invigorate developing Asia's potential growth, whose decline since its 2007 peak explains much of the region's growth slowdown since the global financial crisis. To ensure a healthy future for potential growth, Asia must employ the full range of policy responses to augment labor supply, improve labor productivity, enhance institutional quality, and maintain macroeconomic stability."--Provided by publisher.